2018
DOI: 10.1039/c7tb03223d
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse live cell imaging to monitor doxorubicin release from DNA origami nanostructures

Abstract: Self-assembled DNA nanostructures have attracted significant research interest in biomedical applications because of their excellent programmability and biocompatibility. To develop multifunctional drug delivery from DNA nanostructures, considerable key information is still needed for clinical application. Traditional fixed endpoint assays do not reflect the dynamic and heterogeneous responses of cells with regard to drugs, and may lead to the misinterpretation of experimental results. For the first time, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 25 publications
10
58
0
Order By: Relevance
“…PBS: phosphate‐buffered saline. Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…PBS: phosphate‐buffered saline. Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…Recent years have witnessed structure–function studies on the roles of size and shape on the cellular uptake of origami structures. In 2018, Zeng et al reported the uptake of 2D nanocrosses (with a thickness of ≈2 nm), 2D nanorectangles (with a thickness of ≈2 nm), and 3D nanotriangles (with a thickness of 6.2 nm) of similar hydrodynamic sizes of ≈50 nm by MDA‐MB‐231 breast cancer cells . Despite statistically insignificant differences in cellular uptake between the three doxorubicin (DOX)‐loaded nanostructures during the first 2 days of incubation, 3D nanotriangles enter the cells more abundantly than the other two structures on day 3, based on the intracellular fluorescence levels of doxorubicin (Figure D).…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…It is also important, however, to find correlations between the structures, and the functions in which we are interested, such as the actual release of the drug in the target cells. Zeng and co‐workers used time‐lapse live‐cell imaging to investigate the internalisation of three different DOX‐loaded DNA origami nanostructures, including 3D triangles and flexible 2D rectangles and crosses (Figure C), and tracked drug release for up to 3 days . They found that the 3D triangle showed a significantly enhanced cellular uptake and sustained drug release compared with that of the 2D structures.…”
Section: Dna Nanostructure Uptake and Stabilisation Strategiesmentioning
confidence: 99%
“…Zeng and co-workersu sed timelapse live-cell imaging to investigate the internalisationo f three different DOX-loaded DNA origami nanostructures, including 3D trianglesa nd flexible 2D rectangles and crosses ( Figure 1C), and tracked drug releasef or up to 3days. [14] They found that the 3D triangles howedas ignificantly enhanced cellular uptake and sustainedd rug release compared with that of the 2D structures. It wass imultaneously demonstratedt hat these nanostructures could translocate into the nucleus where the 3D triangled isplayed greater accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation